NEW RECORDS OF ACONTIA CANDEFACTA (HUBNER, 1831) (LEPIDOPTERA: NOCTUIDAE) FROM CROATIA, SLOVENIA AND BOSNIA AND HERZEGOVINA (Acta Entomologica Serbica, 2023)
In this paper, we present new records of Acontia candefacta in Croatia, Slovenia and Bosnia and Herzegovina. From the time of the first records in Croatia in 2019, the species has spread across much of the country and has also become very common in its northern regions. The first observations have been reported for Slovenia and Bosnia and Herzegovina. In Slovenia, the species has been recorded at two localities near the Croatian border, while in Bosnia and Herzegovina, the species has been recorded in two far-apart regions, indicating that it is more widespread in the country.